Analysis of the Law 30407 «Law on Animal Protection and Welfare» in Peru - Vega O., Sulma (2016)
The aim of this paper is to analyze the new Law of Animal Protection and Welfare in Peru which is based on the need to establish a law that promotes the defense and ensures the protection and welfare of animals regardless of species as well as the biodiversity conservation. Furthermore, some scopes of legislations enacted in other American countries and suggestions needed to be implemented in the short to medium term are given.